PENGARUH CR, TATO, NPM, DAN EPS TERHADAP NILAI PERUSAHAAN DI ERA BANI - Sugeng Hariadi , (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to determine the effect of Current Ratio (CR), Total Asset Turn Over, Net Profit Margin (NPM), and Earning Per Share (EPS) on firm value in ASEAN banking in the era of B.A.N.I. This research uses quantitative research – non case by using secondary data. The secondary data used is the annual report of banking companies in ASEAN in 2020-2021. The report is obtained from the official website of each stock exchange in every country in ASEAN. As for other secondary data used in this study in the form of journals, books, and other literature related to research. The results of this study are CR, TATO, NPM and EPS have an effect on Company value.